Maşlāĥah Mursalah dan Dampak Sosial Ekonomi Revitalisasi Pasar Tradisional - Maftuhin, Muhammad Arif; Puspitarini, Tantin (Institut Agama Islam Sunan Giri Ponorogo, 2021)
Traditional markets are places where traders and buyers meet which are marked by direct transactions and price bargaining. While revitalization is a process to revive something that was previously empowered. The impact of revitalizing traditional markets is in the form of social and economic impacts. Then what about the socio-economic impact of traders and buyers after market revitalization? Then how is the mashlahah review of this impact?. This type of research uses qualitative research, this research will understand the social or economic conditions of the community, which later is expected to be able to become input for the general public and government agencies in carrying out policies regarding the revitalization of traditional markets. From this research, it can be underlined that a policy will certainly lead to a conflict and the impact that accompanies it. Socio-economy is something that cannot be separated from people's lives. The perceived social and economic impacts are both direct and indirect. The social and economic impact that became the topic of the most was when the arrangement of the trading booths was changed and grouped according to the merchandise. In this study, it was shown that the benefit was only felt by some components of the community, then others did not really feel it as a result of the many perceived impacts.